Hubungan Stres dan Strategi Coping bagi Mahasiswa Fakultas Teknik di Masa Pandemi Covid-19 - Didit Darmawan; Mohammad Djaelani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The 2019 coronavirus (Covid-19) outbreak has become a global catastrophe that has spread rapidly. To stop the spread of the disease, almost every country has implemented public health measures. Many colleges have turned to online teaching for the safety of academics and students. Students are trapped in a pandemic condition and have to accept the fact that they are not effectively undergoing lectures. Students and lecturers experience disturbances in the education system. This of course creates stress. Therefore, coping strategies to reduce stress are needed to prevent the harmful effects of prolonged stress. The purpose of this study was to determine the relationship between stress and coping strategies. This study uses a quantitative descriptive and correlation research methodology in collecting the required information. The participants of this research are 30 students of the Faculty of Engineering who will participate and answer questions in virtual interviews via zoom. The analytical tool is correlation. The results of the study found that there was a strong relationship between academic stress and coping strategies